Menyekolahkan Anak di Pesantren: Antara Kepentingan Orang tua dan Anak dalam Perspektif Kesejahteraan Sosial - Siti Solechah; Abidah Muflihati; Muhammad Irfai Muslim; Noorkamilah (UIN Sunan Kalijaga Yogyakarta, 2022)
This paper aims to find answers to the phenomenon of increasing interest among urban Muslim communities in sending their children to Islamic boarding schools. The phenomenon is intriguing because there is a tendency for this interest to be driven by pressure or influence from the current cultural trend of sending children to boarding schools. Meanwhile, boarding schools are educational institutions with a strong Islamic character that focus on instilling Islamic values in children. So, what motivates parents to send their children to boarding schools? Is it merely following the cultural trend, or is it an expression of religious consciousness? This paper presents the results of qualitative research based on various data sources (books and articles) that discuss the contributions of boarding schools to the national education system. To analyze this phenomenon, the constructive structuralism theory of Bourdieu is used, where parents' preference for sending their children to boarding schools can be understood from their habitus and capital. The research findings show that the cultural and economic capital possessed by parents significantly influences their tendency to send their children to boarding schools. Furthermore, the social structure of parents can also shape their preference for traditional or modern types of boarding schools Keywords: ; Islamic boarding schools, urban Muslim, cultural trend, Tulisan ini bertujuan untuk menemukan jawab atas adanya fenomena meningkatnya animo masyarakat muslim perkotaan dalam menyekolahkan anaknya ke pesantren. Fenomena menjadi menarik karena ada kecenderungan bahwa animo ini didasari oleh adanya tekanan atau pengaruh dari trend budaya masyarakat saat ini yang cenderung menyekolahkan anaknya ke pesantren. Sementara itu pesantren merupakan lembaga pendidikan bercorak ke-Islaman yang sangat kental dengan penanaman karakteristik anak berdasarkan pada nilai-nilai Islam. Maka apakah yang menjadi motif orang tua menyekolahkan anaknya ke pesantren? Sekedar mengikuti trend budaya, ataukah ekspresi kesadaran keberagamaan? Tulisan ini adalah hasil penelitian kualitatif terhadap sejumlah sumber data (karya), berupa buku dan artikel yang membahas hasil penelitian mengenai kontribusi pesantren untuk khasanah pendidikan nasional. Untuk membaca fenomena tersebut, digunakan teori strukturalisme konstruktif Bourdieu, dimana preferensi orang tua menyekolahkan anaknya ke pesantren dapat dilihat dari habitus dan kapital yang dimiliki oleh orang tua tersebut. Hasil penelitian menunjukkan bahwa kapital budaya dan ekonomi yang dimiliki orang tua sangat besar pengaruhnya terhadap kecenderungan orang tua menyekolahkan anaknya ke pesantren. Dilihat dari struktur sosial orang tua, juga dapat membentuk pola pilihan jenis pesantren, tradisional ataukah modern. Kata Kunci: Muslim Perkotaan, Trend Budaya, Pesantren